EMPLOYABILITY AFTER INITIAL TRAINING: THE FINAL PROFILE IN PHYSICAL EDUCATION (Fiep Bulletin - online, 2013)
The school environment has a peculiar problem that does not present the same way as in vocational courses. The teacher faces a harsh reality when he realizes the school that will operate mainly in public. There are problems related to inadequate teaching materials, spaces not suitable for professional practice guidelines and dissatisfaction with school. In this sense, the research studied the insertion in the labor market, in public and private schools, the graduates of the Bachelor's Degree in Physical Education from a particular IES in São Paulo. The research is descriptive, survey data and the sample of 32 graduates of the year 2012. It was found that 84.5% of graduates are working in the area of ??training, most of which lists the powers in the course of acquiring skills for professional practice. We conclude that the course offered by IES provided an improvement in professional and social life of graduates through its recognition in society and rising wages.
Keywords: Initial training; Physical Education; Egress